Implementation of Green Skills in Vocational Education: Perceptions about Students' and Teachers' Behavioral Activities - Aprillya Anastasia Haloho; Pardjono; Ida Nugroho Saputro; Suyitno; Bayu Ariwibowo (Universitas Pendidikan Ganesha, 2023)
Vocational education has a duty to help green industries and sustainable development in society. However, learning in vocational education still has many shortcomings that must be overcome, given the contribution of a sizable negative impact on the environment. The implementation of green skills in learning is very important as an effort to overcome these problems. This study analyzes the perceptions of teachers and students as learning practitioners towards the implementation of green skills in the form of activity behavior in learning. Ten teachers and eight students were involved as key informants in collecting data through semi-structured interview techniques. Qualitative data were analyzed thematically with the help of NVivo 12 Plus Software. The findings in this study are classified into three main aspects, namely green skills planning activities, green behavior activities during learning, and green skills implementation evaluation. Planning activities related to the formulation of green competency outcomes, infrastructure needs and student readiness. As long as its implementation is oriented towards the behavior of reuse, reduce, repair and recycle. The impact of green behavior that is generated is about student learning comfort, energy-saving behavior and the ability to develop green products. The perceived evaluation is related to improving learning methodologies and building collaboration in class or collaboration with stakeholders, including the green industry, the local green environment service. Besides that, strengthening the competence of green skills-based learning management is very important to do.